1997
DOI: 10.1111/j.1600-0897.1997.tb00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulations of Cytokine Expression in Pregnant Women

Abstract: Cytokine expression is thus finely tuned in peripheral blood during pregnancy, in a previously unexpected complex pattern, related to gestational stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
2
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 43 publications
3
42
2
2
Order By: Relevance
“…Although pregnant women included for our study had no contractions, the spontaneous production of IL-6 by peripheral lymphocytes was quite high. It does not confirm the observations of Tranchot-Diallo et al [10] who stated that IL-6 mRNA levels in peripheral blood mononuclear cells were depressed from the first trimester until the day of parturition. Because basal peripheral blood lymphocytes IL-6 secretion is so high, it probably means that rapidly increasing serum IL-6 concentrations in labor do not originate from activated peripheral blood lymphocytes.…”
Section: Discussioncontrasting
confidence: 55%
“…Although pregnant women included for our study had no contractions, the spontaneous production of IL-6 by peripheral lymphocytes was quite high. It does not confirm the observations of Tranchot-Diallo et al [10] who stated that IL-6 mRNA levels in peripheral blood mononuclear cells were depressed from the first trimester until the day of parturition. Because basal peripheral blood lymphocytes IL-6 secretion is so high, it probably means that rapidly increasing serum IL-6 concentrations in labor do not originate from activated peripheral blood lymphocytes.…”
Section: Discussioncontrasting
confidence: 55%
“…9,15 It could also depend whether control sample was taken from pregnant women at term, during labour5 or in a non pregnant women or in first trimester of pregnancy. 7 As a result of intercellular communication, changes of expression of types and qualities of cytokines occur.…”
Section: Discussionmentioning
confidence: 99%
“…Early placental implantation is alsocharacterized by a cytokine -and humoral-mediated antiinflammatory T-helper cell type (Th) 2-dominated environment which is thought to induce local immunosuppression to the allogeneic fetus and placenta. Consistently, classical Th2 cytokines such as interleukin (IL)-4 and IL-10 are upregulated in the serum of pregnant women [24] as well as at the fetalmaternal interface [25] and were shown to regulate trophoblast invasion [26,27]. Moreover, it is suggested that an overall shift towards proinflammatory Th1 predominance may cause adverse pregnancy outcome such as spontaneous abortion, premature delivery, preeclampsia and intrauterine growth restriction (IUGR) [28].…”
Section: Introductionmentioning
confidence: 98%